Studies in law, politics, and society. Volume 63 - Sarat, Austin (Studies in law, politics, and society., 2014)
The articles in this 63rd volume of Studies in law, politics and society cover cutting edge issues of major interest to policy makers, activists and interdisciplinary law scholars : family law, the way law deals with children, international human rights, and the way law deals with injury and damages claims.